The Nephroprotective Effects of the Allogeneic Transplantation with Mesenchymal Stromal Cells Were Potentiated by ω3 Stimulating Up-Regulation of the PPAR-γ - Andreia Silva de Oliveira; Márcia Bastos Convento; Clara Versolato Razvickas; Bianca Castino; Ala Moana Leme; Rafael da Silva Luiz; Wesley Henrique da Silva; Maria Aparecida da Glória; Tatiana Pinotti Guirão; Eduardo Bondan; Nestor Schor; Fernanda Teixeira Borges (MDPI AG, 2023)
Mesenchymal stromal cells (MSCs) obtained from bone marrow are a promising tool for regenerative medicine, including kidney diseases. A step forward in MSCs studies is cellular conditioning through specific minerals and vitamins. The Omega-3 fatty acids (ω3) are essential in regulating MSCs self-renewal, cell cycle, and survival. The ω3 could act as a ligand for peroxisome proliferator-activated receptor gamma (PPAR-γ). This study aimed to demonstrate that ω3 supplementation in rats could lead to the up-regulation of PPAR-γ in the MSCs. The next step was to compare the effects of these MSCs through allogeneic transplantation in rats subjected to unilateral ureteral obstruction (UUO). Independent of ω3 supplementation in the diet of the rats, the MSCs in vitro conserved differentiation capability and phenotypic characteristics. Nevertheless, MSCs obtained from the rats supplemented with ω3 stimulated an increase in the expression of PPAR-γ. After allogeneic transplantation in rats subjected to UUO, the ω3 supplementation in the rats enhanced some nephroprotective effects of the MSCs through a higher expression of antioxidant enzyme (SOD-1), anti-inflammatory marker (IL-10), and lower expression of the inflammatory marker (IL-6), and proteinuria.